Survey of Some Heavy Metals and Radioactivity in the Dust in A Selected Area in Kirkuk Governorate- Northern Iraq - Khwedim, Kareem; Ahmed, Muaiad Tahir; Najemalden, Mohamed A. (Iraqi Journal of Science, 2022)
Air pollution means the release of pollutants into the atmosphere, which are harmful to human health and the planet as a whole. Almost all air pollutants come from production and energy use. In the present work, an assessment of some heavy metals, natural radioactivity and the quantity of dust fallen in three sites (Tessen, Rahemawa, and Laylan) in Kirkuk Governorate, northern Iraq. Three dust samples were collected from three locations (residential, commercial and industrial areas). The collected samples were analyzed for Cd, Cr, Cu, Ni, Pb, Zn, and radioactivity (Gamma rays). The studied heavy metals (Fe, Ni, Pb, and Zn) exceeded their limits in the atmosphere due to the increase in the number of automobiles, which added pollutants to the atmosphere through the fuel combustion in automobiles. The industrial processes, especially the petroleum industry considered the most dominant in Kirkuk Governorate, and anthropogenic activities also participated. Chromium Cr, Cu and gamma-ray were within the acceptable limits according to the World Nuclear Association (WNA).